An exploration of teacher and school capacity to deliver practicals at O level under the new curriculum for science subjects - Butai, Michael Kokera (Midlands State University, 2020)
The purpose of this study was to explore teacher and school capacity to deliver practicals under the new curriculum for science subjects in Zimbabwe. The study was carried out on a single school in the Midlands Province capital of Gweru in the Lower Gweru area. The main areas under study where teacher and school ability to effectively deliver practical lessons in O-level science under the new curriculum. The other area of study was on the challenges being faced by teachers to effectively incorporate O-level science practicals into the time table in harmony with other subjects. Results were obtained through the use of the questionnaire, interview and observation check list. The principal findings of the research showed that teacher qualification and the type of institute that trained the teacher had a significant impact on teacher ability to deliver practicals. Further findings also revealed that the type of subjects a teacher sat for at O-level had a significant impact on the subjects they would be willing to teach comfortably under the new science curriculum. From the study it was found that though some teachers were doing practicals, this practical work was only done by way of teacher demonstrations with reasons being lack of adequate time on the timetable as well as lack of lab apparatus for the large O-level classes averaging fifty five pupils to use. Looking at the status of the school it was seen that lack of lab apparatus, water sources and stools in relation to class size would significantly affect practical lessons with increased risks of accidents and poor completion rates if learners were grouped. From the findings above it was concluded that the school should have adequately trained teachers for each level, lab apparatus should be sourced while new labs are built, repaired or upgraded where necessary. Failure to do so would see the average public examination science pass rates of the school likely to fall.